Singing Methods to Improve College Students' Arabic Vocabulary - Rizal Munir, Dede; Maftuhah, Maftuhah; Najmi, Irfan; Amin, Saifuddin; Bensar, Muin (Universitas Muhammadiyah Surakarta, 2023)
This research is motivated by the inefficient use of Arabic learning methods, especially in memorizing mufrodat. Many students think that learning Arabic and memorizing mufrodat is difficult and unpleasant, resulting in a lack of interest in learning Arabic. This study has the main objectives of increasing: 1) the level of student learning activity during mufrodat learning; 2) achievement of mufrodat learning outcomes through the application of the singing method. This research was conducted at MIN 2 Purwakarta, Ciawi Village, Wanayasa District, Purwakarta Regency. The research subjects were grade 1 students at MIN 2 Purwakarta in the 2022/2023 school year, which consisted of 16 students. This research is a classroom action research with qualitative and quantitative analysis methods. Data collection techniques include interviews, observation, tests and documentation. The results of this study can be concluded that: 1) The application of the singing method can increase student learning activities, this is indicated by an increase in student activity presentation from 70% to 93%; 2) The application of the singing method can improve student learning outcomes regarding mufrodat baitii for class 1 students at MIN 2 Purwakarta, Ciawi Wanayasa Village, Purwakarta for the 2022/2023 academic year. This is indicated by an increase in learning completeness and the average student achievement during each cycle of actions implemented. 1) The application of the singing method can increase student learning activity, this is indicated by the increase in student activity presentation from 70% to 93%; 2) The application of the singing method can improve student learning outcomes regarding mufrodat baitii for class 1 students at MIN 2 Purwakarta, Ciawi Wanayasa Village, Purwakarta for the 2022/2023 academic year. This is indicated by an increase in learning completeness and the average student achievement during each cycle of actions implemented. 1) The application of the singing method can increase student learning activities, this is shown by the increase in student activity presentations from 70% to 93%; 2) The application of the singing method can improve student learning outcomes regarding mufrodat baitii for class 1 MIN 2 students in Purwakarta, Ciawi Wanayasa Village, Purwakarta, the academic year 2022/2023. This is shown by an increase in learning completeness and the average student learning achievement during each implemented action cycle.